Negative Regulation of Age-Related Developmental Leaf Senescence by the IAOx Pathway, PEN1, and PEN3 - Crane, Renee A.; Cardénas Valdez, Marielle; Castaneda, Nelly; Jackson, Charidan L.; Riley, Ciairra J.; Mostafa, Islam; Kong, Wenwen; Chhajed, Shweta; Chen, Sixue; Brusslan, Judy A. (Frontiers in Plant Science, 2019)
Early age-related developmental senescence was observed in Arabidopsis cyp79B2/cyp79B3 double mutants that cannot produce indole-3-acetaldoxime (IAOx), the precursor to indole glucosinolates (IGs), camalexin and auxin. The early senescence phenotype was not observed when senescence was induced by darkness. The cyp79B2/cyp79B3 mutants had lower auxin levels, but did not display auxin-deficient phenotypes. Camalexin biosynthesis mutants senesced normally; however, IG-transport and exosome-related pen1/pen3 double mutants displayed early senescence. The early senescence in pen1/pen3 mutants depended on salicylic acid and was not observed in pen1 or pen3 single mutants. Quantitation of IGs showed reduced levels in cyp79B2/cyp79B3 mutants, but unchanged levels in pen1/pen3, even though both of these double mutants display early senescence. We discuss how these genetic data provide evidence that IAOx metabolite(s) are playing a protective role in leaf senescence that is dependent on proper trafficking by PEN1 and PEN3, perhaps via the formation of exosomes.